Visions of the modern - Golding, John. (Berkeley : University of California Press, 1994)
A collection of essays on modern art by John Golding. It assembles many of his most important essays: some long out of print, others first published in journals inaccessible to the average reader, while others started life as lectures. Artists featured include Matisse, Picasso, and Brancusi
Guillaume Apollinaire - the painters' friend; Fauvism and the school of Chatou - Post-Impressionism in crisis; two new views of Matisse - a book and an exhibition pioneering Cubism; still-life lives; two Picasso exhibitions - early and late; Leger and the heroism of modern life; Ozenfant; futurism in Venice; supreme suprematist - Malevich; white magic - Brancusi; Picasso's "Gongora"; Picasso and Surrealism; the blind mirror - Andre Breton and painting; Duchamp - the large glass; Arshile Gorky - the search for self; Frank Stella's working space; postscript - interview with Richard Wollheim.
Includes bibliographical references (pages 355-363) and index.
Keywords: Modernism (Art); Art, Modern -- 20th century